An artificial bridge circuit approach between two biological neurons using nanoscale topologies towards paralytic disorders. (May 2023) - Haque, Md Nazmul; Gorre, Pradeep; Jatoth, Deepak Naik; Kumar, Sandeep; Al-Shidaifat, Ala'aDdin; Song, Hanjung
Abstract: The advent of Nanoscale IC technology towards pulse-based neural systems reactivates the dead nervous about restoring the functionality of paralytic disorders. This work reports in first time a design of a novel CMOS biological neuron system, which replaces a dead neuron between two neurons to restore communication in paralyzed individuals. The work binds into three stages: design of a spiking leaky Integrator and Fire (LIF) neuron with refractory period mechanisms, which achieves a low power consumption of 2.4 μW, in the first stage; an adaptive homeostatic synapse with short and long-term spike plasticity, that reconfigure the spiking neuron networks of multichannel sensor electrodes to record the electric signal from the active cell as second stage; the final stage presents a low-power common source current reuse regulated cascode (CS-CR-RGC) TIA for amplifying the weak synapse current signal, which achieves a high gain of 135.71 dBΩ with an optimized noise performance of 0.19 pA/Hz. The entire work is designed and implemented using a CMOS 65 nm commercial process that occupies a die area of 400 μm × 120 μm.